Identification and Transcript Analysis of the TCP Transcription Factors in the Diploid Woodland Strawberry Fragaria vesca - Wei, Wei; Hu, Yang; Cui, Meng-Yuan; Han, Yong-Tao; Gao, Kuan; Feng, Jia-Yue (Frontiers in Plant Science, 2016)
Plant-specific TEOSINTE BRANCHED 1, CYCLOIDEA, and PROLIFERATING CELL FACTORS (TCP) transcription factors play versatile functions in multiple processes of plant growth and development. However, no systematic study has been performed in strawberry. In this study, 19 FvTCP genes were identified in the diploid woodland strawberry (Fragaria vesca) accession Heilongjiang-3. Phylogenetic analysis suggested that the FvTCP genes were classified into two main classes, with the second class further divided into two subclasses, which was supported by the exon-intron organizations and the conserved motif structures. Promoter analysis revealed various cis-acting elements related to growth and development, hormone and/or stress responses. We analyzed FvTCP gene transcript accumulation patterns in different tissues and fruit developmental stages. Among them, 12 FvTCP genes exhibited distinct tissue-specific transcript accumulation patterns. Eleven FvTCP genes were down-regulated in different fruit developmental stages, while five FvTCP genes were up-regulated. Transcripts of FvTCP genes also varied with different subcultural propagation periods and were induced by hormone treatments and biotic and abiotic stresses. Subcellular localization analysis showed that six FvTCP-GFP fusion proteins showed distinct localizations in Arabidopsis mesophyll protoplasts. Notably, transient over-expression of FvTCP9 in strawberry fruits dramatically affected the expression of a series of genes implicated in fruit development and ripening. Taken together, the present study may provide the basis for functional studies to reveal the role of this gene family in strawberry growth and development.